Transbronchial cryobiopsy for diffuse parenchymal lung disease: a state-of-the-art review of procedural techniques, current evidence, and future challenges - Lentz, Robert J.; Argento, A. Christine; Colby, Thomas V.; Rickman, Otis B.; Maldonado, Fabien (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
Transbronchial lung biopsy with a cryoprobe, or cryobiopsy, is a promising new bronchoscopic biopsy technique capable of obtaining larger and better-preserved samples than previously possible using traditional biopsy forceps. Over two dozen case series and several small randomized trials are now available describing experiences with this technique, largely for the diagnosis of diffuse parenchymal lung disease (DPLD), in which the reported diagnostic yield is typically 70% to 80%. Cryobiopsy technique varies widely between centers and this predominantly single center-based retrospective literature heterogeneously de nes diagnostic yield and complications, limiting the degree to which this technique can be compared between centers or to surgical lung biopsy (SLB). This review explores the broad range of cryobiopsy techniques currently in use, their rationale, the current state of the literature, and suggestions for the direction of future study into this promising but unproven procedure.